-9n(4n-3)=0

Simple and best practice solution for -9n(4n-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9n(4n-3)=0 equation:


Simplifying
-9n(4n + -3) = 0

Reorder the terms:
-9n(-3 + 4n) = 0
(-3 * -9n + 4n * -9n) = 0
(27n + -36n2) = 0

Solving
27n + -36n2 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), '9n'.
9n(3 + -4n) = 0

Ignore the factor 9.

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(3 + -4n)' equal to zero and attempt to solve: Simplifying 3 + -4n = 0 Solving 3 + -4n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4n = 0 + -3 -4n = 0 + -3 Combine like terms: 0 + -3 = -3 -4n = -3 Divide each side by '-4'. n = 0.75 Simplifying n = 0.75

Solution

n = {0, 0.75}

See similar equations:

| n=750+22(n-12) | | (2x+3)(3x-2)=6 | | 0=-16t^2+74 | | 12x-51=3 | | 11(y-6)+5(y-7)= | | Ln(3x-1)=1.6 | | 10x=22783 | | Y+5x=23 | | Zy-3=10 | | 6-3(6+2x)=0 | | 0=-16t^2+245 | | 7(y-8)=9y-56 | | 10+5(2-2x)=0 | | h=245+16x^2 | | 245=-16t^2+h | | y=(2y)+15 | | 7x+21x-8=7(4x+9) | | (y^2+4y+4)(y+2)= | | 2x^3=129 | | 8m-7=5m+11 | | z(t)=120(1/2)^t/32760 | | -16t^2-h+245=0 | | 6=1-3z | | 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w |

Equations solver categories